Realization of high Ti plasmas and confinement characteristics of ITB plasmas in the LHD deuterium experiments. (29th August 2018) - Takahashi, H.; Nagaoka, K.; Mukai, K.; Yokoyama, M.; Murakami, S.; Ohdachi, S.; Bando, T.; Narushima, Y.; Nakano, H.; Osakabe, M.; Ida, K.; Yoshinuma, M.; et al.
Abstract: The deuterium (D) operation was initiated in the LHD in 2017. In the first campaign of the D experiments, we successfully extended the high temperature regime in the LHD. The new record of the ion temperature ( T i ) of 10 keV associated with the ion internal transport barrier (ITB) was achieved due to several operational optimization. The thermal confinement characteristics of ITB plasmas were compared between hydrogen and D discharges. The effective ion thermal diffusivity of the ion-ITB plasmas was found to be smaller in the D discharges than that in the H discharges. The profiles of the T i, the electron density, and the impurity of the high T i plasmas strongly depended on the magnetic configuration and these profiles tended to peaked in the inward-shifted configuration. It was also found that the electron thermal confinement of the electron-ITB plasmas was clearly improved in the deuterium case. The GKV simulation showed the linear growth rate of TEM/ITG reduced in the plasmas with D both for the ion ITB and the electron ITB plasmas and qualitatively agreed with the tendency of the change in the thermal diffusivity obtained from the power balance analysis.